Brownfield Entry in Emerging Markets - Meyer, Klaus E.; Estrin, Saul (Journal of International Business Studies, 2001)
This paper focuses on the brown-field entry mode, as a special case of acquisition, in which the resources transferred by the investor dominate over those provided by the acquired firm. We see this mode as having particular relevance for entry strategies in emerging markets. The choice of entry mode is analyzed on the basis of a framework utilizing both resource-based and transaction-cost theories. The resource requirements have to be matched with resources available to the investor through an acquired firm, and the decision has to account for the costs of acquiring and integrating the resources.